A Comparative Assessment of Cross-Sectoral Links in the Ukrainian Timber Industry - Sozanskyy, L. Yo. (Statistics of Ukraine, 2019)
The timber industry is an important intersectoral segment and an element of many production chains. The products of this industry are the raw material base for operation of many units of manufacturing and other economic activities. The purpose of the article is to conduct a comparative assessment of the cross-sectoral links of the Ukrainian timber industry, and to draw relevant analytical conclusions. The main need for assessing the cross-industry relationships of the timber industry is to determine the match and the reciprocal impact of supply and demand on woodworking products. For this purpose, the structure of output and costs (intermediate consumption) of the woodworking industry of Ukraine, Poland, Germany and other EU countries were compared. The information base of the study was the cost-release tables. An empirical study performed by the author reveals that the structure of consumption of timber products with industrial purposes in Ukraine essentially differs from the analogous structure in Poland and Germany by relatively small shares of construction and furniture industry. The revealed structural differences in cross-sectoral links of the timber industry are a core reason explaining why the consumption of timber products by the Ukrainian economy is six times lower than the Polish economy and more than twenty times lower than the German one. As a result, the supply of domestic furniture enterprises and construction sector with input resources is still an empty niche for the domestic timber industry, although a promising one. According to the analysis of the cost structure and dynamics in timber industry of Ukraine, it was found that the cost level of domestic woodworking is the highest among EU countries. This is largely explained by the significant differences in the cost structures (intermediate consumption) of the timber industry of Ukraine and the EU. The latter is dominated by the share of timber products, while in Ukraine it tends to decrease. Also, during 2014–2017, the share of agricultural and forestry products increased in the structure of expenditures of the domestic timber industry, while the share of products and services of retail chains decreased. As a result, there was a decrease in the degree of processing of timber raw materials and deterioration in the manufacturability of production. Hence the need to transform the structure of output in timber industry in a way to increase the output of products for the construction and furniture industries, as well as creating organizational, economic and institutional legal conditions that would contribute to the growth of demand for such products in the domestic and foreign markets.